2011
DOI: 10.1590/s1517-83822011000200047
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and uncommon HPV types in HIV seropositive and seronegative women attending an STI clinic

Abstract: Given the causal relationship between specific types of HPV with cervical cancer and precursor lesions, it is important to identify the viral type involved. The aim of this study is to access the prevalence of HPV types in HIV seropositive and seronegative women. Accordingly, 77 HPV positive cervical samples were obtained from 284 women (seropositive (n=112) and seronegative (n=172) for HIV) who attended a Sexually Transmitted Infection clinic, in Vitoria, Southeastern Brazil. Viral DNA was amplified by PCR us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
(43 reference statements)
0
10
1
Order By: Relevance
“…1). These studies were reported from Rwanda [36,37], Brazil [38][39][40], Nigeria [41,42] Thailand [43], South Africa [44][45][46][47], Zambia [48], Burkinafaso [35,49], Senegal [23] and Colombia [50,51]. There was one study conducted in two countries Burkinafaso and South Africa [52].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). These studies were reported from Rwanda [36,37], Brazil [38][39][40], Nigeria [41,42] Thailand [43], South Africa [44][45][46][47], Zambia [48], Burkinafaso [35,49], Senegal [23] and Colombia [50,51]. There was one study conducted in two countries Burkinafaso and South Africa [52].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The maximum sample size was 1371 [44] and the minimum was 98 [41]. The age of participants ranged from 14 to 73 years [39,50]. Three studies didn't mention the upper age range of the participants [23,36,42] (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is a continuing need for the identification of viral and host factors that modulate the risk of disease progression (11). Possible agents included Herpes viruses among which more recently Epstein-Barr Virus (EBV), have been suspected to participate in cervical carcinogenesis (15, 33, 31, 13). For example, latent infection with EBV has been shown to act as a carcinogenic cofactor in several epithelial cell malignancies (38).…”
Section: Introductionmentioning
confidence: 99%
“…Genotypes 6 and 11, although common at anogenital sites, are considered to be low risk for development of carcinoma, as based on studies of cervical SCC . The prevalence of HPV 6 and/or 11 in the anal canal of men who have sex with men (MSM) has been shown to be 15% in HIV‐negative men and as high as 60% in HIV‐positive men, which is significantly higher than the prevalence observed in the female cervix of ∼10% in both HIV‐positive and ‐negative populations . Therefore, HPV 6 and/or 11 genotypes may be more likely to be present in anal and perianal SCC than in cervical SCC.…”
mentioning
confidence: 99%